INNOVATION TECHNOLOGIES AND METHODS IN TEACHING ENGLISH IN TECHNICAL INSTITUTIONS (American Journal of Business Management, Economics and Banking, 2023)
The article emphasizes the use of contemporary teaching technologies in the learning process, emphasizing in particular the use of interactive teaching strategies and cutting-edge educational tools in the instruction of foreign languages. People need to use international languages in areas such as trade, tourism, international relations between governments, technology, science and media. Therefore, many countries such as Japan, Finland and China frame education policies to teach at least one foreign language at primary and secondary school level.